QR Code–Based Lenticular Flashcards to Improve Fourth-Grade Elementary Students’ Learning Outcomes in Science and Social Studies (IPAS) - Gst. Ayu Erina Juniari; Ni Wayan Rati; Basilius Redan Werang (Indo Green Journal, 2026)
This study was motivated by the low learning outcomes of students in Science and Social Studies (IPAS) due to the lack of innovative and interactive learning media. The purpose of this study was to develop and evaluate the validity, practicality, and effectiveness of QR Code–based lenticular flashcards in improving fourth-grade elementary students’ learning outcomes. This research employed the ADDIE development model, involving two media experts, two material experts, two teachers, and 19 fourth-grade students of SDN 1 Tinga-Tinga as research subjects . Data were collected through questionnaires and tests, and analyzed using descriptive and inferential statistics, including the paired sample t-test. The results showed that the media achieved very high validity (3.87 and 3.90), very good practicality (90% and 89%), and effectiveness, as indicated by the improvement of mean scores from 14.68 to 23.89 and a significance value of 0.000 < 0.05. Therefore, the media is considered feasible and effective, with implications as an innovative technology-based learning alternative in elementary education.